Accounting Standards and Financial Transparency for Public Accountability in Indonesia - Masnawaty Sangkala (PT. Maju Malaqbi Makkarana, 2026)
This study examines the role of accounting standards and financial transparency in strengthening public accountability in Indonesia. Using a descriptive-comparative literature review, this study analyzes six selected journal articles published by Indonesian universities that discuss the implementation of accounting standards, financial reporting quality, accessibility of financial information, accounting information systems, and fraud prevention. The findings reveal that the implementation of accounting standards, including SAK ETAP and PSAK 112, contributes to improving the consistency and reliability of financial reporting. However, differences in reporting capacity, limited accessibility of financial statements, and weaknesses in information systems remain key challenges to achieving transparent and accountable financial governance. The study also highlights the relevance of fraud detection perspectives, particularly the fraud triangle theory, in supporting accountability through early identification of financial reporting risks. These findings indicate that public accountability in Indonesia requires not only compliance with accounting standards, but also stronger financial transparency, accessible reporting, reliable accounting information systems, and improved institutional capacity. The study contributes by positioning accounting standards and financial transparency as an integrated framework for enhancing public accountability in both public and private sector contexts in Indonesia.